Investigating the effect of billboard advertising on company performance: a case of Sable press private limited. - Toma, Evelyn Tendai (Midlands State University, 2017)
The billboard as a medium of advertising has caught up well with advertisers in Zimbabwe and the general public as well. Its main aim is to communicate with road users, pedestrians and drivers. It also aims at reminding customers about a product, attract attention and make them more aware of a product leading to increased purchases. The research was carried out as an investigation on the effect of billboard advertising on company performance focusing more on sales, market share and customer perception at Sable Press Private Limited as they have intentions of adding billboard advertising to their marketing tools. The research aimed to determine if billboard advertising would enhance the sales of Sable Press, to find out if billboard advertising would enhance the market share of Sable Press and also to establish the influence of billboard advertisements on customer perceptions. Major literature came from various billboard advertising authors, this major literature focused more on the effect of billboard advertising on sales, market share and customer perception. The study used descriptive research design to try and get an understanding of findings such as explanations from respondents as to why they would behave in a certain way towards an advert placed on a billboard as well as the different attitudes they had towards a company which advertised on billboards. The researcher also used exploratory research design to shed more light on the real nature of the problem of Sable Press’s poor performance in terms of its sales and its market share as well as suggest possible solutions to new ideas. It also helped the researcher to gain ideas and insights into the effectiveness of billboard advertising. To capture all the desired data for the research, questionnaires and interview guides were designed to cover variables in the conceptual framework. Questionnaires were distributed to the target market which is Sable Press corporate clients and the general public. The interview guides were used to carry out face to face and telephone interviews on Sable Press management staff. The researcher used a sample of 60 questionnaires and 4 interview guides and the data was presented in tabular form as well as on graphs. The major findings showed that most of the respondents would buy a product or service advertised on a billboard and the respondents would also move from one company to the other after being exposed to a billboard advert, also customer perceptions towards a company and its offerings were influenced by billboard adverts. The research concluded that if billboard advertising was to be given a chance, it would indeed enhance a company’s performance which in this research refers to the sales and market share of Sable Press and that billboard adverts influenced customer perceptions. The research also recommended Sable Press to consider adding billboard advertising to their marketing tools as it would provide a significant improvement to their challenge of poor sales and low market share.